Analisis Yuridis terhadap Pertimbangan Hakim dalam Menjatuhkan Rehabilitasi bagi Penyalahguna Narkotika Serta Kendala Penerapannya dalam Sistem Hukum Indonesia - Andika Triyono; Nisa Fadhilah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines judicial considerations in imposing rehabilitation for narcotics abusers and the obstacles in its implementation. The research uses a normative legal method with statutory and case approaches. The results show that judicial considerations include juridical, evidentiary, and sociological aspects, but their application remains inconsistent. Decisions are still dominated by a legalistic approach, resulting in suboptimal rehabilitation. The main issue lies in inconsistent judicial interpretation, leading to sentencing disparities. Obstacles also include limited facilities, weak coordination, and suboptimal integrated assessment. Strengthening judicial guidelines and institutional integration is necessary to improve the effectiveness of rehabilitation.